Prioritizing Psychological Consequences of Online Peer Comparison: A Mixed-Methods Analysis Among Indonesian Youth - Abalorio, Bridget; Sari, Intan; Santoso, Agus (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to identify and prioritize the psychological consequences of online peer comparison among adolescents and young adults using a sequential mixed-methods design.Methods and Materials: The research adopted a two-phase sequential exploratory design. The qualitative phase involved a systematic literature review of studies related to online peer comparison, social media use, and mental health outcomes. Data were analyzed using NVivo 14 through open, axial, and selective coding until theoretical saturation was achieved, resulting in nine major psychological themes. The subsequent quantitative phase utilized a cross-sectional survey of 220 Indonesian participants aged 16–30 years, all active social media users. Participants rated the severity and frequency of each identified psychological outcome using a five-point Likert scale. Data were analyzed using SPSS version 26, employing the Friedman test to establish ranking orders and post-hoc Wilcoxon tests for inferential comparisons.Findings: The Friedman test revealed statistically significant differences among the perceived psychological consequences (χ² = 121.37, p < .001). Self-esteem depletion ranked highest (Mean Rank = 8.62), followed by anxiety and distress (Mean Rank = 8.11) and depression and emotional exhaustion (Mean Rank = 7.95). Mid-ranked outcomes included body image dissatisfaction (Mean Rank = 7.78) and envy and resentment (Mean Rank = 7.45). Cognitive distortion, social isolation, identity confusion, and motivation and productivity decline were comparatively lower in impact. The results suggest that emotional and self-evaluative processes constitute the core mechanisms through which online peer comparison affects psychological well-being.Conclusion: Online peer comparison primarily undermines self-esteem and emotional stability, producing multidimensional effects across emotional, cognitive, and behavioral domains. The findings emphasize the need for targeted interventions promoting self-compassion, emotional regulation, and digital literacy to mitigate comparison-induced distress in youth populations.